AKSIOLOGI MASYARAKAT RIAU - A., Agustianto (Jurnal Ilmu Budaya, 2011)
Axiology is also called philosophy of values, it is a branch of philosophy which deals with values. In a social life of a society, values are the of objects of aims as social convention. It is reflected in that society behavior Riau society has its own values system. It is necessary to discuss to find the meaning axiologically. The material object in the Riau society and the formal object is the axiolgy. Riau society where culture diverse implies in its values system. Riau society applies 3 values systems: value of religious, adat and tradition. These values embody the human of religion, truth, ethical, aesthetic.